Sociopragmatic Analysis Of Presuppositions In Jerome Polin's Youtube Content - Linta Diana Fitri (Cita konsultindo, 2025)
This study aims to analyze the forms and types of presuppositions in Jerome Polin's YouTube video content using sociopragmatic studies. Language not only functions as a means of communication, but also reflects social reality and relationships between individuals. In this context, presupposition is seen as a pragmatic aspect that contains implicit meanings based on shared assumptions between speakers and interlocutors. The method used is descriptive qualitative with data collection techniques in the form of listening, note-taking, and bibliography. The data were taken from a video entitled